Convergence theorem for equilibrium problem and Bregman strongly nonexpansive mappings in Banach spaces - Wiyada Kumam (2018)
© 2015 Taylor & Francis. In this paper, we present an iterative scheme for Bregman strongly nonexpansive mappings in the framework of Banach spaces. Furthermore, we prove the strong convergence theorem for finding common fixed points with the set of solutions of an equilibrium problem.